The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/microorganisms8081226
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Antibiotic Resistance, and Biofilm-Forming Ability of Enterobacteria Isolated from Red Meat and Poultry Preparations

Abstract: A total of 44 samples of beef, pork, and poultry preparations were tested. Average counts (log cfu/g) of enterobacteria were 1.99 ± 0.99 (beef preparations), 1.96 ± 1.44 (pork), 2.09 ± 0.92 (chicken), and 2.17 ± 1.06 (turkey) (p > 0.05). Two hundred enterobacterial strains were identified and 13 genera (21 species) were distinguished, including species that are a significant cause of infection. The most common genera were Escherichia (32.5% of strains), Serratia (17.0%), Hafnia (12.5%), and Salmonella (12.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Various studies refer to lower levels of enterobacteria in poultry, both in Spain, where a figure of 2.89 ± 0.77 log 10 cfu/g was recorded by Buzón-Durán et al [ 4 ], and in other areas within the European Union, with 2 log 10 cfu/g noted by Fraqueza et al [ 38 ]. Previous studies also carried out in north-western Spain [ 3 ] indicated a lower load of enterobacteria in meat preparations based on beef, at 1.99 ± 0.99 log 10 cfu/g, and pork, at 1.96 ± 1.44 log 10 cfu/g. This greater count of enterobacteria in poultry products when compared to foodstuffs of other types may have been an outcome of the higher initial pH in birds’ muscle meat [ 39 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Various studies refer to lower levels of enterobacteria in poultry, both in Spain, where a figure of 2.89 ± 0.77 log 10 cfu/g was recorded by Buzón-Durán et al [ 4 ], and in other areas within the European Union, with 2 log 10 cfu/g noted by Fraqueza et al [ 38 ]. Previous studies also carried out in north-western Spain [ 3 ] indicated a lower load of enterobacteria in meat preparations based on beef, at 1.99 ± 0.99 log 10 cfu/g, and pork, at 1.96 ± 1.44 log 10 cfu/g. This greater count of enterobacteria in poultry products when compared to foodstuffs of other types may have been an outcome of the higher initial pH in birds’ muscle meat [ 39 ].…”
Section: Discussionmentioning
confidence: 84%
“…A certain proportion of meat is eaten in the form of meat preparations. Regulation (EC) 853/2004 defines meat preparations (e.g., minced meat), as fresh meat, including meat that has been reduced to fragments, which has had foodstuffs, seasonings or additives added to it, or which has undergone processes insufficient to modify the internal muscle fibre structure of the meat, and thus to eliminate the characteristics of fresh meat [ 3 ]. Meat preparations are suitable for a range of cooking techniques, and thus satisfy the demands of consumers, who prefer meat products ready to cook, since saving time in the preparation of food has become a priority for most families [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, XDR patterns were identified in 100% of the isolates of K. oxytoca and K. pneumoniae. These MDR Enterobacteriaceae isolates, also referred to as superbugs, are capable of horizontally transferring their resistance genes to other pathogenic microorganisms at various points along the food chain and have few effective treatments for their infections [17,67]. The increasing role of animal-derived food to MDR Enterobacteriaceae, including Enterobacter, Klebsiella, and Serratia, have previously been documented in raw milk, red meat, and chicken meat this trend continues [17,34,[68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…These MDR Enterobacteriaceae isolates, also referred to as superbugs, are capable of horizontally transferring their resistance genes to other pathogenic microorganisms at various points along the food chain and have few effective treatments for their infections [17,67]. The increasing role of animal-derived food to MDR Enterobacteriaceae, including Enterobacter, Klebsiella, and Serratia, have previously been documented in raw milk, red meat, and chicken meat this trend continues [17,34,[68][69][70]. Of these health significances, according to a Centers for Disease Control and Prevention report from 2013, fluoroquinolone-resistant P. aeruginosa and other antibiotic-resistant infections sickened more than two million people each year, with at least 23,000 dying [71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation